LABOR MARKET SEARCH, INFORMALITY, AND SCHOOLING INVESTMENTS. (26th July 2021) - Bobba, Matteo; Flabbi, Luca; Levy, Santiago
Abstract: We develop a search and matching model where jobs can be formal or informal. Workers choose schooling and search for jobs. Firms post vacancies in each schooling market and decide the job's formality status. Upon meeting, workers and firms bargain over wages. The equilibrium size of the informal sector is an endogenous function of labor market fundamentals and institutions. We estimate the model using labor force survey data from Mexico and exploiting the exogenous variation induced by a noncontributory social program. Counterfactual experiments show that eliminating informal jobs increases schooling investments but decreases welfare for both workers and firms.